Protective Effect of Fermented Camel Milk Containing Bifidobacterium longum BB536 on Blood Lipid Profile in Hypercholesterolemic Rats - Khaled M. El-Zahar (Hindawi Limited, 2021)
The present study aimed to investigate synergistic health effects of camel milk and Bif. longum BB536 in rats with diet-induced obesity, impaired lipid profile, and hypercholesterolemia. Wistar rats received a high-fat (HF) diet plus 2 ml/day of either cow’s milk fermented with yogurt culture (CT), camel milk fermented with yogurt culture (CAT), camel milk fermented with Bif. longum BB536 (CAP), mixed cow’s and camel milk fermented with yogurt culture (CCAT), or cow’s milk and camel milk fermented with Bif. longum (CCAP). All fermented milk products significantly reduced HDL, albumin, and total protein. The percentage change in body weight gain was between −40% (CAP) and −24% (CT) and in serum triglycerides between −54% (CCAP) and −37% (CT); for the other parameters, changes caused by CCAP/CT were −40%/−22% (total cholesterol), +29%/+8% (HDL), −73%/−54% (LDL), −54%/−37% (VLDL), −52%/−14% (AST), −53%/−31% (ALT), +43%/+25% (albumin), +37%/+25% (total protein), −48%/−27% (urea), and −34%/−16% (creatinine). Camel or cow’s milk fermented with yogurt culture or Bif. longum significantly improved negative effects of the HF diet on body weight, blood lipid profile, serum proteins, liver and kidney markers, and severity of the metabolic syndrome. Milk and fermentation culture acted synergistically with camel milk and Bif. longum generally showed stronger positive effects./